Offshoring, low-skilled immigration, and labor market polarization - Federico S. Mandelman; Andrei Zlate (Federal Reserve Bank of Atlanta, 2014)
During the last three decades, jobs in the middle of the skill distribution disappeared, and employment expanded for high- and low-skill occupations. Real wages did not follow the same pattern. Although earnings for the high-skill occupations increased robustly, wages for both low- and middleskill workers remained subdued. We attribute this outcome to the rise in offshoring and low-skilled immigration, and we develop a three-country stochastic growth model to rationalize this outcome. In the model, the increase in offshoring negatively affects the middle-skill occupations but benefits the high-skill ones, which in turn boosts aggregate productivity. As the income of high-skill occupations rises, so does the demand for services provided by low-skill workers. However, low-skill wages remain depressed as a result of the surge in unskilled immigration. Native workers react to immigration by upgrading the skill content of their labor tasks as they invest in training.
Keywords: F16; F41; 330; labor market polarization; task upgrading; offshoring; labor migration; heterogeneous agents; international business cycles